2017
DOI: 10.1093/neuros/nyx393
|View full text |Cite
|
Sign up to set email alerts
|

Shunt-Dependent Hydrocephalus After Aneurysmal Subarachnoid Hemorrhage: Predictors and Long-Term Functional Outcomes

Abstract: aSAH patients with shunt-dependent hydrocephalus have significantly poorer long-term functional outcomes. Patients with risk factors for post-aSAH shunt dependence may benefit from increased surveillance, although the effect of such measures is not defined in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 22 publications
3
43
1
1
Order By: Relevance
“…Delayed cerebral ischemia continues to be an important cause of cognitive impairment and disability after aSAH despite accepted aggressive management [27][28][29]. A single center study including 888 aSAH patients found that shunt dependent hydrocephalus was a strong independent risk factor for unfavorable functional outcome [30]. Our nal results also con rm the predictive role of above-mentioned factors.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Delayed cerebral ischemia continues to be an important cause of cognitive impairment and disability after aSAH despite accepted aggressive management [27][28][29]. A single center study including 888 aSAH patients found that shunt dependent hydrocephalus was a strong independent risk factor for unfavorable functional outcome [30]. Our nal results also con rm the predictive role of above-mentioned factors.…”
Section: Discussionsupporting
confidence: 71%
“…Undeniably, more valuable risk variables added into the risk score could improve its predictivity. Treatment methods, shunt-dependent hydrocephalus and delayed cerebral ischemia are three factors that affect the long-term neurological prognosis and cognitive impairment of patients, their role in predicting the prognosis of patients is worthy of recognition [14,30,32,35]. Our PASHPSS have signi cantly improved its discrimination comparing to other risk scores by drawing into these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that high CSF viscosity can lead to an obstructive form of hydrocephalus and/or early CSF circulation disturbances due to arachnoid villi malfunction. 1,5,15,19,20…”
Section: Discussionmentioning
confidence: 99%
“…2,30 Hydrocephalus Requiring a Shunt Several earlier publications have shown that chronic post-aSAH hydrocephalus is related to significant morbidity and readmission to the hospital. 1,5,12,18,29,40 Potential reasons for an impaired outcome after the need for permanent cerebrospinal fluid diversion have been discussed in a recent publication and included elevated intracranial pressure, injury from catheter misplacement, rehemorrhage, and shunt infections. 10 According to our results, hydrocephalus requiring a shunt was a complication that was prominent among elder- 2) 38 (72 (<1) 14 (2) 9 (2) 89 (15) ly patients.…”
Section: Delayed Cerebral Vasospasm and Ischemiamentioning
confidence: 99%